Invasive imaging modalities in a spontaneous coronary artery dissection: when “believing is seeing” - Mehmedbegović, Zlatko; Ivanov, Igor; Čanković, Milenko; Perišić, Zoran; Kostić, Tomislav; Maričić, Bojan; Krljanac, Gordana; Beleslin, Branko; Apostolović, Svetlana (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous coronary artery dissection (SCAD) is a rare but increasingly recognized cause of acute coronary syndrome (ACS) with recent advancements in cardiac imaging facilitating its identification. However, SCAD is still often misdiagnosed due to the absence of angiographic hallmarks in a significant number of cases, highlighting the importance of meticulous interpretation of angiographic findings, and if needed, additional usage of intravascular imaging to verify changes in arterial wall integrity and identify specific SCAD pathoanatomical features. Accurate diagnosis of SCAD is crucial, as optimal management strategies for patients with SCAD differ from those with atherosclerotic coronary disease. Current treatment strategies favour a conservative approach, with intervention reserved for cases with ongoing ischemia, patients with high-risk coronary anatomy or hemodynamic instability. In this paper, we provide a preview of invasive imaging modalities, classical angiographic and intravascular imaging hallmarks that may facilitate proper SCAD diagnosis.